The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1210/jc.2010-0441
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Treatment for Aggressive Pituitary Tumors: Correlation of Clinical Outcome with O6-Methylguanine Methyltransferase (MGMT) Promoter Methylation and Expression

Abstract: We conclude that medical therapy with temozolomide can be helpful in the management of life-threatening pituitary tumors that have failed to respond to conventional treatments. The optimal duration of treatment in patients with stabilization or reduction of tumor size has not been established, and long-term follow up studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
6
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 39 publications
5
148
6
5
Order By: Relevance
“…The alkylating compound, temozolomide, recently demonstrated a significant response against aggressive pituitary adenomas and carcinomas (19,37,38). A recent relatively large cohort study (nZ24) (19) demonstrated that immunohistochemically low MGMT expression predicts a better response to temozolomide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alkylating compound, temozolomide, recently demonstrated a significant response against aggressive pituitary adenomas and carcinomas (19,37,38). A recent relatively large cohort study (nZ24) (19) demonstrated that immunohistochemically low MGMT expression predicts a better response to temozolomide.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have argued that an immunohistochemical MGMT expression analysis is not clinically useful in predicting tumor responses to temozolomide therapy (20,37,38). One possible explanation of the controversy is the acquisition of temozolomide resistance due to the loss of MSH6 expression during temozolomide treatments (19,20,39).…”
Section: Discussionmentioning
confidence: 99%
“…More studies of temozolomide in NS treatment involving larger populations is needed. [18][19][20][21] …”
Section: Discussionmentioning
confidence: 99%
“…Despite these encouraging results with temozolomide showing longterm control in 40% of patients (Bush et al 2010, Raverot et al 2010, some tumours develop secondary resistance during the follow-up (McCormack et al 2009, Raverot et al 2010. The development of new therapeutic options is particularly necessary for pituitary carcinomas resistant to temozolomide .…”
Section: :6mentioning
confidence: 99%